Problems with Destination-Based Corporate Taxes and the Ryan Blueprint - Avi-Yonah, Reuven S.; Clausing, Kimberly (Columbia Journal of Tax Law, 2017)
With the election of Donald Trump and the Republican Party’s domination of Congress, House Speaker Paul Ryan’s blueprint for fundamental tax reform requires more careful analysis. The Ryan blueprint combines reduced individual rates with a destination-based cash flow type business tax applicable to all businesses. The destination-based business tax at the center of the blueprint has several major problems: It is incompatible with our WTO obligations, it is incompatible with our tax treaties, and it will not eliminate the problems of income shifting and inversions it is designed to address. In addition, these proposals generate vexing technical problems that are not easily fixed as well as significant political problems. Finally, due to the tax rates that have been proposed, the plan is likely to generate large revenue losses and a less progressive tax system. We conclude by recommending better tax policy solutions to our current corporate tax problems.